STUDI FENOMENOLOGI PENGALAMAN KELUARGA MERAWAT ANGGOTANYA YANG MENDERITA HALUSINASI DI RUMAH SAKIT JIWA JAMBI - Vevi Suryenti Putri (Universitas Baiturrahim, 2016)
Background:Clients with negative impacts such hallucinations can injure themselves, other people and can damage the environment. Facing such a condition is necessary for the role and efforts of family members so as not to endanger the client and the others around him. Hallucinations diverse client behavior will lead to a stressor for the family and will certainly cause problems for his family. The purpose of this research is to gain a deep understanding of the experience of caring for family members who suffer from hallucinations Mental Hospital Jambi in 2015. Method:This type of research is conducted qualitative research with phenomenological study deskrifitif. Participants in this study is the nuclear family members perform maintenance on their families who suffered from hallucinations that have been selected according to predetermined criteria that amounted to 7 participants. The sampling method with purposive sampling with data analysis methods Colaizzi. Test data using the membercheck Credibility, transferability, Dependability, Comfirmability.Result: Results from this study identified four themes, these are: 1) The type of maintenance performed family members in the home, 2) The issue of perceived family for caring, 3) family to solve the problem by seeking the help of medical personnel and personnel non-medical, 4) Hope family in service and the patient's health. Research recommendations for nursing mental problems that make early detection of mental disorders in the community in order to improve the health status of the community and do a home visit by a cadre of mental health Menthal formed through the training of Community Health Nursing (CMHN), the training BC-CMHN and IC-CMHN .